The Impact of Daily Discrimination on Sleep/Wake Problem Trajectories Among Diverse Adolescents. Issue 5 (9th June 2021) - Xie, Mingjun; Yip, Tiffany; Cham, Heining; El‐Sheikh, Mona
Abstract : This study examines how everyday discrimination is associated with 6‐day trajectories of sleep/wake problems, operationalized as sleep disturbance and daytime dysfunction, among 350 diverse adolescents ( M age = 14.27, SD = 0.61, 69% female; 22% African American, 41% Asian American, 37% Latinx; 24% multiethnic/racial; across participating schools, 72% of students eligible for free/reduced price lunch) in the Northeastern United States. Adolescents encountering discrimination experienced changes in sleep/wake problem trajectories (i.e., significant increases in same‐day sleep/wake problems), whereas adolescents reporting no discrimination experienced no changes in trajectories (Cohen's ds = .51–.55). Multiethnic/racial (compared to monoethnic/racial) adolescents experiencing everyday discrimination reported greater same‐day sleep/wake problems, yet steeper decreases in sleep/wake problems suggesting stronger impact coupled with faster return to baseline levels.